(untitled) (Academicia Globe: Inderscience Research, 2021)
This research work shows the differences and similarities of vowel sound system in three languages: English, German and Uzbek. There are vowels sounds in any language, but their number is not equal.According to the family of the languages there are some similarities, such as English and German belong to Indo-European languages and their phonetic system has the same structures. However, Uzbek is from Turkic languages and it totally differs from English and German.